Danger signal adenosine via adenosine 2a receptor stimulates growth of Porphyromonas gingivalis in primary gingival epithelial cells. (12th February 2014) - Spooner, R.; DeGuzman, J.; Lee, K.L.; Yilmaz, Ö.
Summary Extracellular signaling during inflammation and chronic diseases involves molecules referred to as 'Danger Signals' (DS), including the small molecule adenosine. We demonstrate that primary gingival epithelial cells (GEC) express a family of G‐protein coupled receptors known as adenosine receptors, including the high‐affinity receptors A1 and A2a and low‐affinity receptors A2b and A3. Treatment of Porphyromonas gingivalis‐infected GEC with the A2a receptor‐specific agonist CGS‐21680 resulted in elevated intracellular bacterial replication as determined by fluorescence microscopy and antibiotic protection assay. Additionally, A2a receptor antagonism and knockdown via RNA interference significantly reduced metabolically active intracellular P. gingivalis. Furthermore, analysis of anti‐inflammatory mediator cyclic AMP (cAMP) following A2a receptor selective agonist CGS‐21680 stimulation induced significantly higher levels of cAMP during P. gingivalis infection, indicating that adenosine signaling may attenuate inflammatory processes associated with bacterial infection. This study reveals that the GEC express functional A2a receptor and P. gingivalis may use the A2a receptor coupled DS adenosine signaling as a means to establish successful persistence in the oral mucosa, possibly via downregulation of the pro‐inflammatory response.